Dialog religijny chrześcijan i muzułmanów w Polsce. Instytucje kościelne działające na rzecz porozumienia międzyreligijnego - PWKO, ALDONA MARIA (Annales Missiologici Posnanienses, 2010)
The religion of Islam in Poland still wakes the fear of society before terroristic attempts. This is an result of the low state of knowledge. Some people still duplicate the stereotype, that Muslim has to be a terrorist. The migrations of population in present world causes that also on the streets of Polish cities we can met Muslims practicing their religion. Catholic church in Poland keeps the dialogue and good relations with Muslims, including such institutions as Mutual Catholic and Muslim Council or Committee for Inter-Religious Dialogue.